(untitled) (Journal of Bangladesh Academy of Sciences, 2023)
The experiment was conducted during February to May, 2019 at the research farm of Bangladesh Institute of Nuclear Agriculture, Mymensingh-2202. The objective of the study was to evaluate the growth, reproductive characteristics, yield and yield components of four similar durated mungbean genotypes, namely BARI Mung-2, Binamoog-2, MB-29, and MB-43. At most of the growth stages, the mutant MB-29 showed superiority in terms of growth parameters such as total dry matter, leaf area index, absolute growth rate, relative growth rate, and net assimilation rate whilst MB-43 showed the inferiority. Furthermore, MB-29 outperformed the other three genotypes in yield attributing features, resulting in a higher seed yield than the other three genotypes. In comparison, the MB-43 mutant showed the lowest value for the yield parameters. The seed yield correlated positively and significantly with leaf area, total dry matter, absolute growth rate, and number of pods plant-1. J. Bangladesh Acad. Sci. 47(1); 101-108: June 2023